Empowering rural economies: a community-centric sustainable ecotourism model - Teruki, Neilson (Asian Scholars Network, 2024)
Tourism is a key global industry that impacts millions of lives and has significant potential to drive development. The growing interest in spending leisure time in natural settings and increased environmental awareness has fueled the rapid expansion of ecotourism, now one of the fastest-growing segments in the tourism industry. Unlike traditional mass tourism, ecotourism aims to foster wildlife conservation and promote economic growth, especially in developing countries. The characteristic features of ecotourism include a focus on natural attractions, wildlife, and wilderness habitats, with small-scale operations that are generally low-impact and easier to establish. Ecotourism's success largely depends on active community participation and can offer direct benefits while mitigating pressures from unsustainable resource exploitation. This study explores the Bakun Dam area in the Belaga District to evaluate its potential as a sustainable ecotourism model with community involvement. It aims to address several key objectives, including evaluating local tourist attractions, assessing social and cultural aspects, reviewing infrastructure facilities, and developing a sustainable ecotourism model that involves community participation. The methodology employs a quantitative approach supported by qualitative insights. Data collection instruments include questionnaires, interview guides, and observations, with respondents comprising local authorities, visitors, business owners, and local residents. Simple random sampling ensures a fair representation of the population, and the results are analyzed through descriptive methods focusing on frequencies and distribution. The expected outcomes of this study are multifaceted. By developing a sustainable ecotourism model, it aims to enhance the socioeconomic conditions of local communities, creating employment opportunities, encouraging entrepreneurship, and promoting the sale of local products. The model also seeks to foster community involvement, leading to greater conservation efforts and sustainable practices. This approach can guide national tourism policies, positioning the tourism sector as a significant contributor to the country's GDP. Furthermore, the model's success could generate a positive feedback loop, encouraging similar ecotourism projects across Malaysia and supporting broader sustainable development goals.